The Dago Elos Conflict in Bandung City (2016–2023) - Prima Junika Putra Hendranata; Amung Ahmad Syahrir; Mardani (Postgraduate Program of the State Islamic Institute of Palopo, 2026)
This study explores the social dynamics experienced by the residents of Dago Elos, Bandung, in their efforts to defend land rights from 2016 to 2024. The agrarian conflict involving local communities and third parties with historical land claims has sparked various forms of resistance, community solidarity, and both legal and social advocacy practices. Employing a qualitative approach through case study methods, in-depth interviews, and participatory observation, the research reveals that Dago Elos residents exhibit strong social resilience through collective identity strengthening, mobilization of local culture, and cross-community collaboration within advocacy networks. These dynamics reflect not only a land struggle but also a broader crisis of representation within legal and urban planning systems that often marginalize indigenous and local populations. This study underscores the significance of grassroots movements in the pursuit of social justice and the defense of living spaces.